READY TO LEARN: THE IMPACT OF THE MORNING BLAST PHYSICAL ACTIVITY INTERVENTION ON ELEMENTARY SCHOOL STUDENTS - Tingting Xu; Erik Jon Byker; Monica Rae Gonzales (Universiti Malaysia Pahang, 2017)
Objective: The purpose of this study was to investigate the effects of a physical activity intervention programme, named "Morning Blast", on elementary school students' math learning and daily physical activity. The Morning Blast intervention programme was a 16-week cardiovascular endurance emphasized physical activity program that students voluntarily participated in before the school day. Participants that volunteered, did so for the duration of the program. Methods: This mixed-methods study included seven educators and 83 students (n=90). The students were all children who were enrolled in Grades 3, 4, and 5 in a semi-rural elementary school in the United States. Data were collected through focus-group interviews, surveys, quantitative analysis of step counts, and from quasi-experimental research design. Results: Students in the experimental group were found to have: (1) increased scores on math standard score, (2) greater confidence in their academic ability, and (3) had more accumulated steps compared to students in the control group. Students in the experimental group also reported that they were more "ready to learn" after completing the physical activity intervention. This finding was also confirmed by their teachers. Conclusion: This study demonstrates how an increase in physical activity during the morning time has positive benefits for students throughout the school day.